Skull trepanation in ancient Peru - Lastres, Juan B. (1959)
The trephined skulls of ancient Peru, with polychrome Paracas cloths, beautiful Moche ceramics, the mummies carefully enfardeladas and artistic ceremonial vessels of silver and gold, are the pride of the domestic and foreign museums. They are the best representatives of our country, dumb and conspicuous ambassadors testify missing high cultures.